Case Report: Hypopituitarism Presenting With Nonconvulsive Status Epilepticus - Li, Huimin; Xu, Lina; Yang, Fengbing; Jia, Longbin; Cheng, Hongjiang; Liu, Wei (Frontiers in Neurology, 2021)
Introduction: Hypopituitarism is defined as one or more partial or complete pituitary hormone deficiencies. Nonconvulsive status epilepticus (NCSE) refers to a state of continuous or repetitive seizures without convulsions. In this paper, we review a case of an old female patient with hypopituitarism who presented with NCSE, which is rare in the clinic. Case Report: This paper describes a 67-year-old female patient with hypopituitarism who presented as NCSE. She had surgical resection of pituitary tumor half a year before the seizures and did not get regular hormone replacement therapy. She presented general convulsive status epilepsy as the initial symptom and got sedation and antiepileptic drug in the emergency room. The seizure was terminated but the patient fell in coma in the following days. The patient had magnetic resonance imaging (MRI) and other inspects, and EEG showed epileptic discharges. Combining these clinical symptoms and examinations, we made the diagnosis of NCSE. Finally, she regained consciousness after the treatment with diazepam. Conclusion: This case report and literature review investigated the possible mechanism of hypopituitarism presenting with NCSE.